Exploring Preservice Science Teachers’ Socioscientific Reasoning Competence - Çite, Süleyman; Ünal, Ahmet; Şahingöz, Selçuk (Kastamonu Egitim Dergisi, 2025)
Purpose: Contemporary science education standards underscore the importance of scientific literacy. To this end, science education researchers have been discussing what scientific literacy entails in a globalized world. A recent approach defines scientific literacy not only as the ability to comprehend and apply science concepts but also as the competence to construct arguments about complex, science-based societal issues. This requires scientifically literate individuals to go beyond science concepts and examine societal issues from multiple perspectives, such as economic, social, and ethical, a practice known as socioscientific reasoning. Undoubtedly, developing students' socioscientific reasoning depends on having science teachers who are themselves competent socioscientific reasoners. In this respect, this study aims to document the socioscientific reasoning competencies of preservice science teachers through open-ended tasks incorporating societal issues. Design/Methodology/Approach: To assess preservice science teachers’ socioscientific reasoning competencies, an open-ended response task with two different socioscientific scenarios was designed and administered to 76 third and fourth year teacher candidates. Responses were analyzed with using inductive analysis method. Through constant comparison method, the responses of students were categorized into three level competency. Findings: The results show that while preservice teachers understood the complexity of these societal issues, their reasoning was naive in approaching the issues from the perspectives of different stakeholders, appreciating the need for further inquiry, and skeptically examining the issue. Highlights: The study concludes with implications for preservice science teacher education programs.